(untitled) - Thomson Course Technology; Thomson Course Technology (Boston, Mass., 2006)
Part of the new Succeeding in Business Series, this text prepares students to solve real-life business problems using Microsoft Office 2003 applications
Keywords: Microsoft Office; Microsoft Word; Microsoft Excel; Microsoft Access; Microsoft PowerPoint; Microsoft Outlook